An efficient biochar synthesized by iron-zinc modified corn straw for simultaneously immobilization Cd in acidic and alkaline soils. (15th December 2021) - Yang, Tingting; Xu, Yingming; Huang, Qingqing; Sun, Yuebing; Liang, Xuefeng; Wang, Lin; Qin, Xu; Zhao, Lijie
Abstract: Synthetic functional biochar using agricultural waste as raw materials not only serves as an effective means for recycling waste but can also be employed for the remediation of heavy metal contaminated soil. However, the associated effect and mechanism underlying the immobilization of functional biochar in acidic and alkaline soils remain unclear. In this study, a novel iron-zinc oxide composite modified corn straw (Fe/Zn-YBC) was prepared and applied for the remediation of cadmium-contaminated acidic and alkaline farmland soils. The results showed that the addition of Fe/Zn-YBC increased the pH, cation exchange capacity (CEC), and dissolved organic carbon (DOC) in acidic soil, while increased the pH and DOC in alkaline soil. After immobilization for 42 d, the DTPA-Cd content in acidic and alkaline soils treated with Fe/Zn-YBC decreased by 12.77 %–57.45 % and 23.73 %–52.50 %, respectively. Fe/Zn-YBC treatment promoted the transformation of the exchangeable fraction into the Fe/Mn oxyhydroxide fraction of Cd, and increased the abundance and diversity of bacterial communities in the two soils. Furthermore, the SEM-EDS, XRD and FTIR results for Fe/Zn-YBC separated from the test soils showed that the distribution of Cd adsorbed on Fe/Zn-YBC was positively correlated with Fe, Zn, and O. Additionally, the Cd complexes (CdCO3, CdZnFe2 O4 and CdO) detected on Fe/Zn-YBC indicated that the primary immobilization mechanism of Fe/Zn-YBC involved the complexation of Cd and Fe, Zn oxides, and the precipitation of Cd and CO3 2− in acidic and alkaline soils. The efficient remediation capacity and associated mechanism for this novel functional biochar provide insights for improved remediation of heavy metal contaminated farmland soil. Highlights: Modified biochar effectively reduced the available Cd in acid and alkaline soils. Oxygen-containing group, Zn-O, and Fe-O are the main bonds to immobilize Cd. . Immobilization of Cd in soil via direct and indirect interactions.